Noninfectious lung complications after allogeneic haematopoietic stem cell transplantation. Issue 5 (3rd May 2018) - Bergeron, Anne; Chevret, Sylvie; Peffault de Latour, Régis; Chagnon, Karine; de Margerie-Mellon, Constance; Rivière, Frédéric; Robin, Marie; Mani, Jean; Lorillon, Gwenael; Socié, Gérard; Tazi, Abdellatif
Epidemiological data on late-onset noninfectious pulmonary complications (LONIPCs) following allogeneic haematopoietic stem cell transplantation (HSCT) are derived exclusively from retrospective studies and are conflicting. We aimed to evaluate prospectively the incidence, risk factors and outcomes for LONIPCs. All consecutive patients scheduled to receive allogeneic HSCT between 2006 and 2008 at a university teaching hospital in France were screened for inclusion in the study. Eligible patients were those surviving at day 100. Among 243 screened patients, 198 patients were included in the analysis. The median (interquartile range) follow-up was 72.3 (15.2–88.5) months. 55 LONIPCs were diagnosed in 43 patients. Bronchiolitis obliterans syndrome (n=22) and interstitial lung disease (n=12) were the most common LONIPCs. At 36 months after inclusion, the estimated cumulative incidence of LONIPCs was 19.8% (95% CI 14.2–25.3%). The estimated median survival after the diagnosis of LONIPCs was 78.5 months (95% CI 20.0–not reached). Based on a multivariate Cox model, a history of chest irradiation anytime prior to HSCT, a history of pneumonia within 100 days post-HSCT and a low mean forced expiratory flow at 25–75% of forced vital capacity at day 100 were associated with the development of LONIPCs. Our data provide clues to identify patients at high risk of developing LONIPCs. These patients should be targeted for close monitoring to provide earlier LONIPC treatment or prophylactic treatment. Chest irradiation, pneumonia and low FEF 25–75% predict lung complications after allogeneic bone marrow transplantation http://ow.ly/pGel30j61Da